About the geometrical stability of the marginal terms in variation series - Algimantas Aksomaitis (Lietuvos Matematikos Rinkinys)
It was proved that the logistic minimum is geometrically min-stable, positional statistics  X(kN) ,  k > 1 are not geometrically stable, common minimum and maximum distributions are not asimptotically independent as the sample size is geometrical.